Strategi Penguatan Integrasi JARLATSUH IPDN Untuk Meningkatkan Kompetensi Dan Karakter Praja - Ismail, Nanang (UIR Press, 2025)
This study outlines a strategy for strengthening the integration of Teaching, Training, and Nursing (Jarlatsuh) at IPDN to improve the competence and character of cadets (Praja). Based on program issues, overlapping calendars, and inconsistent standards, this study aims to demonstrate similarities in Jarlatsuh integration across policy, process, and outcomes; identify drivers/inhibitors; and design a measurable integrative strategy package. The method used was a sequential mixed methods approach: document audits, surveys of cadets and lecturers. Analysis was conducted using a shared view linking input, process, and output, accompanied by an USG (Urgency, Seriousness, and Growth) assessment for priority sorting. The results revealed three key findings: first, cross-functional coordination and interoperability of academic training and nursing data are weak, resulting in inconsistent character development; second, standard operating procedures (SOPs) and calendars are not synchronized across campuses; and third, performance monitoring focuses on compliance, rather than competency achievement. Recommendations: It is recommended to establish an IPDN Rector's Decree on the Establishment and Governance of an Integrated Jarlatsuh Data Warehouse. This policy creates a single official database for the assessment of teaching, training, care, and graduate tracking. With a single database, evaluations are integrated, and every improvement decision is based on the same, up-to-date, and easily traceable evidence.